Sports policy factors leading to international sporting success - de Bosscher, V. (2007)
This digest is a summary report of a study to compare and analyse sport structures, policy and performance in six nations. The study developed from a concern about the lack of a model for comparing the efficiency and effectiveness of the ever-larger investments being made in high performance sport across the world. The research has been managed, and the report edited, by a consortium of researchers from the three nations involved in the first phase of the study - Belgium (Flanders), Netherlands and the UK. As the research gained momentum, the study broadened out to include Canada, Italy, Norway and the French-speaking part of Belgium (Wallony). The full report is being produced in book form and will be published in 2007. If you have any comments or questions about the study or would like additional copies of the Digest, please contact any member of the SPLISS Consortium: